2022
DOI: 10.1093/cei/uxac049
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisantigen-specific T-cell responses in smear-negative pulmonary tuberculosis patients

Abstract: Despite recent improvements in microbial detection, smear negative TB remains a diagnostic challenge. In this study, we investigated the potential discriminatory role of polychromatic flow cytometry of M. tuberculosis antigen-specific T cells to discriminate smear negative TB from health controls with or without latent TB infection, and non-TB respiratory illnesses in an endemic setting. A cross-sectional study was conducted on HIV negative, newly diagnosed smear-positive PTB (n=34), smear-negative/Gene Expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Besides, it has been observed that the expression of Ki-67 would decrease following treatment [18,19]. The heightened Ki-67 expression in CD4 + and CD8 + T cell subpopulations following in vitro restimulation with MTB antigen in PTM patients suggested a greater burden of mycobacterium antigen in slow responders, hinting at the possibility of PTM being a chronic infectious disease involving both innate and acquired immunity in response to TB antigen [20]. The disparity in CD4 + and CD8 + T cell subset activation implied that immune dysregulation might be a characteristic of PTM.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been observed that the expression of Ki-67 would decrease following treatment [18,19]. The heightened Ki-67 expression in CD4 + and CD8 + T cell subpopulations following in vitro restimulation with MTB antigen in PTM patients suggested a greater burden of mycobacterium antigen in slow responders, hinting at the possibility of PTM being a chronic infectious disease involving both innate and acquired immunity in response to TB antigen [20]. The disparity in CD4 + and CD8 + T cell subset activation implied that immune dysregulation might be a characteristic of PTM.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the proportion of sputum smear-negative TB in these patients was the lowest. TB patients with smear-negative were found to have higher levels of immune cells and IFN- γ [ 41 , 42 ]. As mentioned above, both glycemic control and statin use can improve immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…T uberculosis (TB) continues to pose a considerable global health burden, and smear-negative pulmonary tuberculosis (SNPT) represents a significant proportion of TB cases. 1 , 2 Smear-negative pulmonary tuberculosis is defined by the absence of detectable bacteria in sputum smears, despite clinical and radiological indications of pulmonary TB. 3 The limited bacterial presence in SNPT complicates diagnosis using conventional techniques, resulting in delays in treatment initiation and heightened risk of disease transmission.…”
mentioning
confidence: 99%